Amonio cuaternario de quinta generación en odontología: ¿Eficaz contra el SARS-CoV-2? - Cayo-Rojas., César (2021)
Coronaviruses are a family of lipid-enveloped, single-stranded, positive RNA viruses that may be present in vertebrates, causing respiratory, enteric, liver, and neurological diseases.1 There are two members of this family that have previously affected humans severely, the severe acute respiratory syndrome coronavirus (SARS-CoV) and the Middle East respiratory syndrome coronavirus (MERS-CoV), related to respiratory diseases.2